Online Training Development on English Storytelling for Entrepreneurs - Kunto Imbar Nursetyo, S.Pd., M.Pd (Southeast Asian Journal on Open and Distance Learning, 2023)
This study aims: 1) to know the stages of development of "Online Training Development on English Storytelling for Entrepreneurs", and 2) to find out the effectiveness of the results of "Online Training Development on English Storytelling for Entrepreneurs". Research on the development of digital books using the ADDIE development model consists of 5 stages: 1) analysis; 2) design, 3) development, 4) implementation and 5) evaluation. The results of the study concluded that: 1) researchers conducted the development of "Online Training Development on English Storytelling for Entrepreneurs", 2) the design and development of training in this network using the ADDIE model. 3) the results of feedback from as many as 83% of training participants were prepared to take part in online training. 72% of online training participant responded positively to online learning in English Storytelling for Entrepreneurs. Technology received a positive response of 75% and aid services received a positive response of 83%.